2013
DOI: 10.1364/oe.21.010070
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ray cluster rendering for interactive integral imaging system

Abstract: In this paper, we present an efficient Computer Generated Integral Imaging (CGII) method, called multiple ray cluster rendering (MRCR). Based on the MRCR, an interactive integral imaging system is realized, which provides accurate 3D image satisfying the changeable observers' positions in real time. The MRCR method can generate all the elemental image pixels within only one rendering pass by ray reorganization of multiple ray clusters and 3D content duplication. It is compatible with various graphic contents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In the figure, red color represents higher MTF value, while blue color represents lower MTF value. The MTF of [Jiao et al 2013] is shown in the left image of Figure 13, while our result is shown in the right image of Figure 13. The result can demonstrate that the sub-pixel based light field reconstruction method can achieve higher spatial-resolution than pixel based light field reconstruction method [Jiao et al 2013].…”
Section: Spatial Resolution Analysismentioning
confidence: 84%
See 3 more Smart Citations
“…In the figure, red color represents higher MTF value, while blue color represents lower MTF value. The MTF of [Jiao et al 2013] is shown in the left image of Figure 13, while our result is shown in the right image of Figure 13. The result can demonstrate that the sub-pixel based light field reconstruction method can achieve higher spatial-resolution than pixel based light field reconstruction method [Jiao et al 2013].…”
Section: Spatial Resolution Analysismentioning
confidence: 84%
“…For comparison, under the same condition that the horizontal angular resolution is 8, both the height and width between adjacent light field ray is as 8 times of the pixel's size, so the spatial resolution under regular pixel based light field reconstruction only achieves (1000/8)x(1000/8)=125x125. [Jiao et al 2013] Here, the angular resolution can be represented by the number of view-dependent reconstructed light field views. Figure 4: Illustration of specific design for micro lens array.…”
Section: Lens Array Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental result demonstrates the high speed performance of our method. In the aspect of reconstructed spatial resolution, [Jiao et al 2013] achieves only 125x125 while the proposed method can obtain 250x250 at the same integral image size.…”
Section: Methods Overviewmentioning
confidence: 99%